Diastereoselectivity in the Aza-Michael Reaction of Chiral α-Methylbenzylamines with α,β-Unsaturated Carbonyl Compounds - Kour, M.; Gupta, R.; Saini, R.; Bansal, R. K. (SynOpen, 2018)
The aza-Michael reaction of (S)-(–)- and (R)-(+)-α-methylbenzylamines with trans-cinnamaldehyde and other α,β-unsaturated carbonyl compounds occurs with 52–98% diastereoselectivity (de); however, in the reaction with crotonaldehyde, the de is lower (20–38%). In the products obtained from the reaction with α,β-unsaturated aldehydes, the de could be determined on the basis of the relative intensities of the aldehydic protons of the two diastereomers. Theoretical investigations of the reaction of (S)-(–)-α-methylbenzylamine with trans-cinnamaldehyde at the DFT (B3LYP/6-31+G*) level reveal that the diastereomer formed from the attack of the amine on the Re face is thermodynamically more stable. The calculations also show that the aldehydic proton of this diastereomer is expected to be more deshielded, which on the basis of the 1H NMR spectrum is the major product.
Keywords: aza-Michael reaction; α-methylbenzylamine; diastereoselectivity; trans-cinnamaldehyde; DFT calculations